Neopterin, the Cell-Mediated Immune Response Biomarker, in Inflammatory Periodontal Diseases: A Narrative Review of a More than Fifty Years Old Biomarker - Heneberk, Ondrej; Wurfelova, Eliska; Radochova, Vladimira (Biomedicines, 2023)
Neopterin is a biomarker of the activation of cellular immunity. The purpose of this review is to summarise neopterin metabolism, methods of its detection, and its role in inflammation, focusing on periodontal inflammatory diseases. This derivative of guanosine is a non-enzymatic product of 7,8-dihydroneopterin oxidation caused by free radicals which protect activated macrophages from oxidative stress. Various methods, usually based on enzyme-linked immunosorbent essay, high-performance liquid chromatography, or radioimmunoassay were developed for the isolation of neopterin. A wide spectrum of diseases and conditions are known to affect neopterin levels, including cardiovascular, bacterial, viral, and degenerative diseases, as well as malignant tumours. Neopterin levels were found to increase in subjects with periodontitis, especially when the oral fluid and gingival crevicular fluid were evaluated. These findings confirm the role of activated macrophages and cellular immunity in periodontal inflammatory diseases. The gingival crevicular fluid and the oral fluid appear to be the most valuable biologic fluids for the evaluation of neopterin levels in periodontitis. For gingival crevicular fluid, neopterin can be determined as the concentration or the so-called total amount. Nonsurgical periodontal treatment was associated with a decrease in neopterin levels, but an increase was also reported, suggesting the possible role of macrophages in the resolution of the periodontal lesion.
Keywords: periodontitis; inflammation; macrophages; neopterin; cellular immunity